2013
DOI: 10.2478/s11686-013-0185-z
|View full text |Cite
|
Sign up to set email alerts
|

A survey of biting midges of the genus Culicoides Latreille, 1809 (Diptera: Ceratopogonidae) in NE Bulgaria, with respect to transmission of avian haemosporidians

Abstract: This study presents data from a molecular survey of the species of the genus Culicoides from the region of Kalimok Field Station (NE Bulgaria) and haemosporidian parasites occurring in them in order to investigate the host-parasite specificity of haemosporidians to their dipteran vectors. The identification of Culicoides spp. was carried out by morphological and molecular-genetic methods. We collected and analysed 230 individuals of the genus Culicoides. Nine species were found. Eight species were identified m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 33 publications
4
52
0
Order By: Relevance
“…C. circumscriptus and C. festivipennis harboured one and two Haemoproteus lineages, respectively. The lineage H_CIRCUM03 differed with one nucleotide base from previously reported H_CULCIR01 recorded in the studied area (Bobeva et al 2013). …”
Section: Resultsmentioning
confidence: 46%
See 3 more Smart Citations
“…C. circumscriptus and C. festivipennis harboured one and two Haemoproteus lineages, respectively. The lineage H_CIRCUM03 differed with one nucleotide base from previously reported H_CULCIR01 recorded in the studied area (Bobeva et al 2013). …”
Section: Resultsmentioning
confidence: 46%
“…Moreover, recent studies have revealed that C. alazanicus, together with C. circumscriptus and C. festivipennis, demonstrate ornithophilic feeding preferences (Lassen et al 2012;Pettersson et al 2012;Bobeva et al 2014). In addition, haemosporidian parasites have been previously detected in the latter two species (Ferraguti et al 2013;Synek et al 2013;Bobeva et al 2013). The degree of associations between haemoproteids, bird hosts and vector species in the studied area suggests C. alazanicus, C. circumscriptus and C. festivipennis as potential vectors of avian haemosporidians in SE Europe.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Most previous studies on avian haemosporidians have focused on their interactions with bird hosts, especially with respect to species diversity, prevalence and local transmission in different geographical regions (Waldenström et al ., ; Dimitrov et al ., ). Few recent studies report potential associations between Haemoproteus species and vectors of the genus Culicoides (Martinez‐de la Puente et al ., ; Santiago‐Alarcon et al ., , ; Bobeva et al ., , Synek et al ., ). However, the roles of species of Culicoides in the transmission of certain haemoproteids, and in the geographic distribution of these parasites, remain poorly known.…”
Section: Introductionmentioning
confidence: 99%